Aid and state-building, Part I: South Korea and Taiwan. - Bizhan, Nematullah (Third World Quarterly, 2018)
Under what conditions does foreign aid in the aftermath of war foster state-building? This article argues that institutional legacy and continuity and the politics of aid may matter. In the aftermath of war, for an aid regime to reinforce state-building, it may need to ensure continuity in the strength of the state and to use recipient mechanisms and finance policies that generate a greater state capacity. The existence and continuity of a Weberian state may increase the likelihood of effective state-building. If the state is relatively strong, with a Weberian bureaucracy, aid can further reinforce it when aid is spent through national systems or is aligned with local priorities, with efforts to ensure that the recipient leaders reinforce state effectiveness by implementing policies that may require greater state capacity. Evidence for this argument is provided through pairwise comparison of state-building patterns between South Korea and Taiwan.